Instilling Mental Toughness Through the Ad-Menstren Model to Manage Competitive Anxiety Among Jambi University Gymnasts - Muhammad Gilang Aryadiandra; Wawan Junresti Daya; Mohd Adrizal (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2026)
This study analyzed the role of mental toughness cultivation through the Ad-Menstren Model in helping athletes of the Gymnastics Student Activity Unit at Jambi University to manage competitive anxiety. A descriptive quantitative survey was conducted with 15 athletes selected through purposive sampling. The instrument was a 35-item Likert-scale mental toughness questionnaire based on self-efficacy, self-esteem, and self-confidence indicators. Data were analyzed through validity testing, reliability testing, descriptive statistics, and score categorization. All items were valid, and reliability was very high, with Cronbach's Alpha of 0.967. The mean score was 115.27 with a standard deviation of 14.048. Category distribution showed 4 athletes in the very high category, 2 in high, 7 in low, and 2 in very low. The findings indicate that the Ad-Menstren Model can support self-strength recognition, positive thinking, concentration, and emotional regulation under competitive pressure.